Reactivity of Aromatic Phosphorus Heterocycles – Differences Between Nonfunctionalized and Pyridyl‐Substituted 2, 4, 6‐Triarylphosphinines1. Issue 2 (11th December 2014) - Pfeifer, Gregor; Ribagnac, Philippe; Le Goff, Xavier‐Frédéric; Wiecko, Jelena; Mézailles, Nicolas; Müller, Christian
Abstract: Detailed studies on the reactivity of 2‐(2′‐pyridyl)‐4, 6‐diphenylphosphinine (2 ) towards CF3 SO3 H and sulfur have been performed, and the results were compared with those for nonfunctionalized 2, 4, 6‐triphenylphosphinine derivatives. Substantial differences between these heterocycles were observed, and the reaction products could be characterized crystallographically. The reactions of 2, 4, 6‐triarylphosphinine sulfides with methanol led to different products, which could be characterized by NMR spectroscopy and X‐ray crystal structure analysis. Interestingly, the outcomes of these transformations strongly depend on the presence of an additional donor functionality within the phosphorus heterocycle as well as the nature of the solvent and the reaction temperature. DFT calculations were performed to rationalize the different reaction pathways. Abstract : Substantial differences in reactivity towards methanol have been observed for 2, 4, 6‐triarylphosphinine derivatives. The outcomes of the transformations strongly depend on the presence of additional donor functionalities within the phosphorus heterocycle as well as the nature of the solvent and the reaction temperature. DFT calculations were performed to rationalize the observed reaction pathways.